2015
DOI: 10.1016/s1474-4422(15)00050-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in autism spectrum disorder: brain structure and function across the lifespan

Abstract: Over the past decade, in-vivo MRI studies have provided many invaluable insights into the neural substrates underlying autism spectrum disorder (ASD), which is now known to be associated with neurodevelopmental variations in brain anatomy, functioning, and connectivity. These systems-level features of ASD pathology seem to develop diff erentially across the human lifespan so that the cortical abnormalities that occur in children with ASD diff er from those noted at other stages of life. Thus, investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
294
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 377 publications
(316 citation statements)
references
References 149 publications
(161 reference statements)
17
294
1
4
Order By: Relevance
“…Regarding intensity correction, in the MRC AIMS database used in this study [Ecker et al, 2012, 2013, 2015], a standardization procedure based on quantitative imaging [Deoni et al, 2008] was used to minimize inter‐site variance and improve the signal‐to‐noise contrast. However, as the between‐site analysis in “Experiment 1: Effect of Acquisition Site” section suggests, this strategy still results in variance that makes it easier to distinguish scanning sites than diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding intensity correction, in the MRC AIMS database used in this study [Ecker et al, 2012, 2013, 2015], a standardization procedure based on quantitative imaging [Deoni et al, 2008] was used to minimize inter‐site variance and improve the signal‐to‐noise contrast. However, as the between‐site analysis in “Experiment 1: Effect of Acquisition Site” section suggests, this strategy still results in variance that makes it easier to distinguish scanning sites than diagnostic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Structural MRI were analysed from 136 adult, right‐handed males (68 with ASD and 68 matched controls) with no significant mean differences in age and full‐scale IQ, acquired from the centres contributing to the UK Medical Research Council Autism Imaging Multi‐centre Study (MRC AIMS) [Ecker et al, 2012, 2013, 2015] and recruited by advertisement. In this work, only participants recruited at the Institute of Psychiatry, King's College London (LON) and the Autism Research Centre, University of Cambridge (CAM) were included where an equivalent set of images were acquired from each participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early findings from several structural magnetic resonance imaging studies have shown that toddlers with ASD, aged on average 2-4 years, have a larger brain volume than typically-developing children, an effect that levels off by 6-8 years [35,36]. These findings contribute to the notion that the trajectory of brain maturation in ASD is atypical and involves an early period of overgrowth, with each brain region having its distinct trajectory [35,36].…”
mentioning
confidence: 92%
“…Early findings from several structural magnetic resonance imaging studies have shown that toddlers with ASD, aged on average 2-4 years, have a larger brain volume than typically-developing children, an effect that levels off by 6-8 years [35,36]. These findings contribute to the notion that the trajectory of brain maturation in ASD is atypical and involves an early period of overgrowth, with each brain region having its distinct trajectory [35,36]. Further structural neuroimaging studies have revealed ASD to be a disorder with general and regional alterations in brain size, while functional neuroimaging studies have highlighted changes in connectivity between brain regions in ASD patients [35,[37][38][39].…”
mentioning
confidence: 99%